Reactions to Short-Term Adaptation Pressures During Transformation in Party-States: The Case of China - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, 2010)
How do external and internal adaptation pressures influence the transformation of the party-state system in China? How susceptible is the Chinese systemtransformation to those impacts? This paper deals with the sensitivity of the transformation process on the short-term under different external conditions: both during the period of global economic growth and the period of global crisis. Our approach is institutional and systemic, in view of the postulates of the Interactive Party-State (IPS) model (Csan di, 2006). We shall conclude that the transformation process demonstrates sensitivity to short-term impacts that cause fluctuations in the direction and speed of the transformation process both during growth and decline. Moreover, we shall reveal that sensitivity to- and consequences of internal and external adaptation pressures show different spatial characteristics.
Keywords: F5; D78; R58; J08; O15; E24; 330; party-state model; short-term shocks; system transformation; global crisis; migration; economic policy reactions; prefectures; Wirtschaftsordnung; Parteiensystem; Systemtransformation; Schock; Wirtschaftskrise; International; Wirtschaftliche Anpassung; China